Gradable semantics in Russian and Tuvan proverbs - Kolesnikova, Svetlana M. (The New Research of Tuva, 2022)
The article’s objective is to correlate the paremiac paradigms of Russian and Tuvan languages. Within the semantic structure of units we consider here, of special importance are the gradasemes (i.e. semes that indicate the degree or grade of how strongly the quality is expressed, and of its qualitative and quantitative description). We examine the semantic specifics of Russian and Tuvan proverbs. The presence of identical objects for comparison in both languages allows us to trace such paremies which are similar in form, but different in content and do a comparative study of these.The gradable paradigm in paremies rests upon the antonymic dominant lexemes (‘clever’—’stupid’, etc.) They possess an invariant meaning of a qualitative feature without preserving expression. Other units are of gradable character, which takes shape in accordance with dominating components, and are markedly emotional. Qualitative adjectives in proverbs (or in their explanations) indicate polarity in meaning and match the object’s characteristics (‘big’ vs. ‘small’, ‘high’ vs. ‘low’, etc.) To measure the degree of the quality’s expression in proverbs with gradable semantics, we have to possess a tool which may show the degree of deviation from it.In proverbs, comparisons perform the functions of style and gradability. Zoonyms and ornitonyms, for instance, act as symbols which add a certain degree to the quality they express, in order to emphasize a certain (most commonly, negative) personal feature. In Russian proverbs, the wolf or the snake stand for cruelty, and the fox, for cunning, while in Tuvan, the cow (inek) is a symbol of persistence, the camel (teve), of clumsiness, etc. Some animals have common association in both languages, such as the ‘garrulous’ jackdaw (saaskan). The presence of such gradable and evaluative semantics, coupled with a value-based classification, in a language allows us to distinguish between units which have the meaning of general assessment or private tastes –– such as psychological, sensoric, or ethical ones.
Keywords: proverbs; gradable semantics; gradaseme; gradable evaluation; Tuvans; Tuvan folklore; Tuvan proverb